A Case Report on Dapsone Syndrome - Simrun, Darga; Koteshwar, K; Rajavardhan, Thamineni; Bhavani, Mopuri; Reddannal, Languluri; Sreedhar, V (Indian Journal of Pharmacy Practice)
Dapsone is useful for treating a variety of infectious, immunological and hypersensitivity disorders. Commonly encountered adverse effects of this drug include dose unrelated (idiosyncratic) skin hypersensitivity reactions and dose-related haemolytic anemia and methemoglobinemia. Dapsone Hypersensitivity Syndrome (DHS) can be considered as a manifestation of DRESS (Drug Rash with Eosinophilia and Systemic Symptoms) syndrome. DRESS is an adverse reaction that can be seen with the use of many drugs such as dapsone, sulfonamides, allopurinol, cyclosporine, azathioprine, minocycline, antiviral drugs, anticonvulsant and gold salt. This report refers to 45 year old female patient was brought to the hospital with chief complaints of Fever chills and rash all over the body since 1 week. One year prior to current admission she was prescribed with dapsone 100 mg/day on suspection of leprosy and found the hypersensitivity reaction on usage of dapsone for 4 weeks. We report a case on Dapsone syndrome with skin rashes all over the body and fever and effectively treated with Corticosteroids.
Keywords: Dapsone syndrome; DRESS syndrome; Hypersensitivity reactions; Prednisolone.